Bullying verbal menyebabkan depresi remaja SMA Kota Yogyakarta - Gitry Marela; Abdul Wahab; Carla Raymondalexas Marchira (Berita Kedokteran Masyarakat (BKM), 2017)
Verbal bullying can cause depression in high school adolescents in Yogyakarta cityPurposeThis study aimed to determine the differences in the incidence of depression in high school adolescents who received bullying and who did not received bullying in Yogyakarta city.MethodThis study used a cross-sectional design involving 210 high school adolescents in Yogyakarta city. The independent variable was bullying and dependent variable was depression. Data analysis included univariable, and bivariable analysis using Chi-square tests and multivariable analysis with logistic regression tests.ResultsThe types of bullying most experienced by adolescents was verbal bullying by 47.3%, physical bullying by 29.8%, social bullying by 20.2% and cyber bullying by 2.7%. The bivariable analysis showed a significant correlation between bullying and depression. Bivariable analysis showed a significant correlation between the victims of bullying with depression. Adolescents who received bullying had 1.5 times greater potential to become depressed than adolescents who did not receive bullying.ConclusionThe incidence of depression in high school adolescents who received bullying was higher than adolescents who did not receive bullying.